NILAI-NILAI RELIGIUSITAS PADA TRADISI MAIN BESAN TOAH - Rosyidi, Rosyidi (Al-Amien Prenduan University, Sumenep, 2024)
The tradition of Main besan toah Â after the wedding, is a tradition preserved by the community of Pragaan Daya Pragaan Sumenep, which is carried out after the wedding reception, this event takes the form of a visit from both families of the bride, in this research the researcher explore the religious values that exist in this activity, using qualitative research methods. The results of this research show that through this tradition the community has carried out the teachings of the Islamic religion in the form of commands to get to know each other, to build friendship between the extended families of the bride, to share the blessings, by bringing souvenirs to the host. At the same time, the bride extended family is practicing religious teachings, namely repaying kindness with something better, because when the man comes to the woman's side bringing lots of gifts, or the group is quite large, the woman will respond with kindness better than that.